2022
DOI: 10.1002/ehf2.13854
|View full text |Cite
|
Sign up to set email alerts
|

Association of chronic heart failure with mortality in old intensive care patients suffering from Covid‐19

Abstract: Aims Chronic heart failure (CHF) is a major risk factor for mortality in coronavirus disease 2019 (COVID‐19). This prospective international multicentre study investigates the role of pre‐existing CHF on clinical outcomes of critically ill old (≥70 years) intensive care patients with COVID‐19. Methods and results Patients with pre‐existing CHF were subclassified as having ischaemic or non‐ischaemic cardiac disease; patients with a documented ejection fraction (EF) were subclassified according to heart failure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Lower platelet counts in the CKD group compared to the NKF group (247.3 ± 102.5 vs. 299.3 ± 115.7 [1 × 10 3 /mm 3 ], p = 0.036) may result from inflammation and subsequent disseminated coagulation. Higher concentrations of lactates in patients with CKD compared to the group with preserved renal function correspond with a higher mortality rate, which is reported in another study concerning risk factors in COVID-19 patients [36]. In the performed univariable logistic regression, CKD was also significantly associated with mortality (OR 4.044, 95%CI: 1.723-9.490, p = 0.013).…”
Section: Discussionsupporting
confidence: 56%
“…Lower platelet counts in the CKD group compared to the NKF group (247.3 ± 102.5 vs. 299.3 ± 115.7 [1 × 10 3 /mm 3 ], p = 0.036) may result from inflammation and subsequent disseminated coagulation. Higher concentrations of lactates in patients with CKD compared to the group with preserved renal function correspond with a higher mortality rate, which is reported in another study concerning risk factors in COVID-19 patients [36]. In the performed univariable logistic regression, CKD was also significantly associated with mortality (OR 4.044, 95%CI: 1.723-9.490, p = 0.013).…”
Section: Discussionsupporting
confidence: 56%
“…In support of this approach, previous research has indicated that considerations regarding life-sustaining treatment significantly influence prognosis [20]. In addition, although not evaluated in this study, an older age is considered a significant risk factor for severe outcomes from COVID-19 [29,30], with chronic disease [4,31], a higher degree of frailty [12], a higher SOFA score [6,32], and elevated levels of inflammatory markers [33,34] generally being associated with worse clinical outcomes. These complexities call for a comprehensive management strategy that addresses both the direct effects of COVID-19 and the broader underlying health issues that affect older patients, especially those requiring intensive interventions such as CRRT.…”
Section: Discussionmentioning
confidence: 69%
“…40 However, a study conducted by Bruno et al examined the impact of the pre-existing chronic heart failure on the clinical outcomes of critically ill elderly patients (≥70 years) receiving intensive care for COVID-19, and concluded that the pre-existing condition did not influence 30-day mortality. 41 Due to immune dysregulation, chronic liver diseases are believed to put affected individuals at risk of adverse outcomes following infection with SARS-CoV-2. Recent reports have indicated that patients with the pre-existing chronic liver diseases have a high mortality rate for COVID-19, with an associated mortality rate of 39.8%.…”
Section: Discussionmentioning
confidence: 99%